Alkaline pretreatment and enzymatic saccharification of oil palm empty fruit bunch fiber for ethanol production 1) Pengolahan awal dengan basa NaOH dan sakarifikasi enzimatis serat tandan kosong kelapa sawit (TKKS) untuk produksi etanol - Yanni SUDIYANI; Kiky C SEMBIRING; Hendris HENDARSYAH; Syarifah ALAWIYAH (Menara Perkebunan, 2010)
Abstract Alkaline pretreatment of oil palm empty fruit bunch (EFB) fiber was conducted to improve enzymatic sacchari-fication of EFB fiber for ethanol production.  EFB as one of the major biomass wastes from palm oil industry is a complex lignocellulosic material consists of 41.3 – 46.5% of cellulose, 25.3 – 33.8% of hemicellulose and 27.6 – 32.5% of lignin.  Alkali pretreatment of EFB using NaOH 1 N with temperature at 30 and 600C and reaction times of 30, 60, 90, 120 and 150 minutes were investigated.  Furthermore, the enzymatic saccharification of pretreated EFB was examined. The pretreated substrate was subjected to an enzymatic saccharification using meicelase (10, 20 and 40 FPU/g substrate) at 400C, pH 4.5, 100 rpm for conversion of cellulose and hemicellulose in palm oil EFB to monomeric sugars. The alkali pretreatment of EFB using NaOH can significantly improve the enzymatic saccharification of EFB by removing more lignin and hemicellulose and increasing its accessibility to hydrolytic enzymes.  The results showed that the optimum pretreatment condition was NaOH 1 N at 300C and 90 minutes with the optimum component loss of lignin and hemicellulose was 45.8  % and 35.6  % respectively.  The saccharification of EFB pretreated by NaOH 1 N (at 300C and 90 minutes) for 45 hours and pH 4.5 resulted in optimum saccharification of 63.8 %.  Abstrak Pengolahan awal (pretreatment) serat tandan kosong kelapa sawit (TKKS) dengan basa NaOH telah dilakukan untuk meningkatkan sakarifikasi enzimatik TKKS menjadi etanol.  TKKS merupakan bahan lignoselulosa yang terdiri dari selulosa 41,3– 46,%,  hemicellulosa 25,3 – 33,8% dan lignin 27,6 – 32,5%. Pretreatment TKKS dilakukan dengan NaOH 1 N dengan variasi suhu 300 dan 600C dan variasi waktu 30, 60, 90, 120 dan 150 menit.  Konversi selulosa dan hemiselulosa hasil pretreatment TKKS menjadi gula dilaku-kan dengan sakarifikasi enzimatik menggunakan enzim meiselase (10, 20 dan 40 FPU/g substrat) pada suhu 400C, pH 4,5 dengan shaker 100 rpm.  Pretretament TKKS dengan basa   NaOH   dapat   meningkatkan   sakarifikasi enzimatik dengan berkurangnya lignin dan hemiselulosa secara signifikan dan memudahkan masuknya enzim hidrolitik.  Hasil pretreatment dengan NaOH 1N pada suhu 300C dan 90 menit menunjukkan kondisi optimum untuk penghilangan lignin dan hemiselulosa berturut-turut sebesar 45,8  % and 35,6  %.  Hasil sakarifikasi optimum yaitu 63,8 % dicapai setelah 45 jam sakarifisi pada pH 4,5.